1996
DOI: 10.1038/380708a0
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the posterior morphogen nanos for germline development in Drosophila

Abstract: In many animal groups, factors required for germline formation are localized in germ plasm, a region of the egg cytoplasm. In Drosophila embryos, germ plasm is located in the posterior pole region and is inherited in pole cells, the germline progenitors. Transplantation experiments have demonstrated that germ plasm contains factors that can form germline, and germ plasm also directs abdomen formation. Genetic analysis has shown that a common mechanism directs the localization of the abdomen and germline-formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
206
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(212 citation statements)
references
References 28 publications
5
206
0
1
Order By: Relevance
“…We have shown that transplanted nos pole cells never migrate into the host gonads (15). To our surprise, their ability to enter the gonads was restored by suppressing apoptosis.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…We have shown that transplanted nos pole cells never migrate into the host gonads (15). To our surprise, their ability to enter the gonads was restored by suppressing apoptosis.…”
Section: Resultsmentioning
confidence: 83%
“…Maternal nos mRNA is enriched in germ plasm, and its protein product is partitioned into pole cells when they are formed and remains detectable in these cells throughout embryogenesis (14). Nos is required in pole cells for their proper migration into the embryonic gonads (15,16). Within pole cells, Nos is involved in maintaining transcriptional quiescence (17) and is also required for maintenance of a germ-line-specific chromatin status that correlates with transcriptional inactivity (18).…”
mentioning
confidence: 99%
“…Nanos proteins are involved in the regulation of various development processes. In Drosophila, nanos regulates differentiation of the anterior-posterior body axis, primordial germ cell migration, oogenesis and spermatogenesis (Wang and Lehmann, 1991;Wang et al, 1994;Kobayashi et al, 1996;Forbes and Lehmann, 1998;Bhat, 1999;Deshpande et al, 1999). hNanos1 is abundant in germ-line stem cells (Jaruzelska et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nanos is an evolutionarily conserved RNA-binding protein that is essential for germ cell development (7). In Drosophila, Nanos forms a complex with another RNA-binding protein, Pumilio, and represses the translation of the hunchback, cyclin B, and hid mRNAs thereby establishing embryonic polarity, mitotic quiescence, and suppression of apoptosis, respectively (8)(9)(10).…”
mentioning
confidence: 99%